Comparative Analysis of PCR and LIPA Method for HCV Genotypes Screening - Akhter, Asma; Javed, Mahwish; Imran, Muhammad (BioScientific Review, 2019)
Abstract Background: Hepatitis C virus (HCV) is a major health problem worldwide. About 6% of the population of Pakistan is suffering from HCV infection. HCV has a high mutation rate and consists of seven genotypes and sixty-seven subtypes. Genotype information of patients infected with HCV is significant for its treatment. Methods: In this study, 416 HCV serum samples were collected and HCV prevalence rate was studied in different districts of Punjab, Pakistan. Nested PCR and INNO LIPA HCV-II were used for HCV genotyping and their respective performance was evaluated. This study was conducted by the approval of Lahore Clinical Laboratory and Research Centre situated at Shadman, Lahore. Results: The highest prevalence of HCV was found in Shekhupura district followed by Bhakkar, Narowal and Okara districts, respectively. In Punjab, the most prevalent genotype was 3a (70.29%), followed by genotype 1 (5.47%), untypable genotypes (5.44%) and genotype 3a/3b (4.64%). Nested PCR was found to be more reliable than INNO LIPA-II. Nested PCR results were more accurate and only 5 samples remained untypable whereas 33 samples could not be typed by LIPA method. Conclusion: This study was focused on the comparative analysis of Nested PCR and LIPA method for screening HCV genotypes and their prevalence in different districts of Punjab, Pakistan. HCV genotyping is important since different genotypes require different therapeutic treatments. In Punjab, 3a is the most prevalent genotype followed by non-typable genotypes. LIPA is the most commonly used HCV genotype assay but this study found Nested PCR to be a highly sensitive and cost-effective method in this regard. This study can lead to the better selection of genotyping methods and treatment.